Dedifferentiation-like progression of breast carcinoma: report of a case showing transition from luminal-type carcinoma to triple-negative carcinoma with myoepithelial features - Tajima, Shogo (Int J Clin Exp Pathol, 2015)
Certain genetic events that occur at various stages of carcinogenesis can result in phenotypic changes. In breast carcinoma, these changes may occur either in situ, at the primary invasive site, or at a distant metastatic site. This report presents a case of dedifferentiation-like progression of breast carcinoma showing transition from luminal-type carcinoma to triple-negative carcinoma (i.e. negative for estrogen receptor, progesterone receptor, and HER2) with myoepithelial features. An 87-year-old woman was referred to us from another hospital for surgery. Preoperative ultrasonography revealed a mass measuring 16 × 12 × 8 mm. Following partial mastectomy, gross examination revealed a whitish tumor on the cut surface measuring 15 × 10 × 8 mm. Histopathological investigation revealed a predominant high-grade carcinoma containing some short spindle-shaped cells and expressing p63, muscle-specific actin, and alpha smooth muscle actin. The tumor also showed decreased expression of pan-cytokeratin and increased expression of vimentin on immunohistochemistry. Estrogen receptor was not detected by immunostaining. A high Ki-67 labeling index and diffuse nuclear accumulation of p53 were observed in the high-grade carcinoma. In the peripheral area, low-grade carcinoma with estrogen receptor expression was observed, but appeared displaced by the high-grade carcinoma. The high-grade carcinoma exhibiting myoepithelial carcinoma-like morphology and molecular phenotype was deemed to be carcinoma showing dedifferentiation-like changes arising from the peripherally situated pre-existing low-grade carcinoma. Thus, follow-up ought to be mandatory, considering the presumably aggressive nature of the predominant carcinoma showing dedifferentiation-like changes in this case.